Whole-Body Electromyostimulation to Fight Osteopenia in Elderly Females: The Randomized Controlled Training and Electrostimulation Trial (TEST-III) - Simon von Stengel; Michael Bebenek; Klaus Engelke; Wolfgang Kemmler (Journal of Osteoporosis)
Whole-body electromyostimulation (WB-EMS) has been shown to be effective in increasing muscle strength and mass in elderly women. Because of the interaction of muscles and bones, these adaptions might be related to changes in bone parameters. 76 community-living osteopenic women 70 years and older were randomly assigned to either a WB-EMS group (n=38) or a control group (CG: n=38). The WB-EMS group performed 3 sessions every 14 days for one year while the CG performed gymnastics containing identical exercises without EMS. Primary study endpoints were bone mineral density (BMD) at lumbar spine (LS) and total hip (thip) as assessed by DXA. After 54 weeks of intervention, borderline nonsignificant intergroup differences were determined for LS-BMD (WB-EMS: 0.6±2.5% versus CG -0.7±2.5%, P=.051) but not for thip-BMD (WB-EMS: -1.1±1.9% versus CG: -0.8±2.3%, P=.771). With respect to secondary endpoints, there was a gain in lean body mass (LBM) of 1.5% (P=.006) and an increase in grip strength of 8.4% (P=.000) in the WB-EMS group compared to CG. WB-EMS effects on bone are less pronounced than previously reported effects on muscle mass. However, for subjects unable or unwilling to perform intense exercise programs, WB-EMS may be an option for maintaining BMD at the LS.